Peningkatan Kompetensi Dosen Dalam Pembimbingan Proposal Tesis Mahasiswa Magister: Pendekatan Workshop Dan Mentoring Intensif - Emiliana Sri Pudjiarti; Noor Rosyadi; Dian Murdianingsih (Universitas 17 Agustus 1945 Semarang, 2026)
This community service activity aims to improve lecturers' competence in supervising master's student thesis proposals through interactive workshops and intensive mentoring at the Adias Institute of Technology and Business, Pemalang. The activity was carried out in two online sessions via Zoom Meeting on April 11 and May 21, 2026, involving 24 participants consisting of 12 active supervisors and 12 master's students. The approach used refers to Kolb's experiential learning model, including socialization of needs, workshops on academic standards and feedback techniques, mentoring simulations, and formative evaluations based on competency rubrics. The results of the activity showed a significant increase in all indicators of mentoring competence with an average increase of 51.7 percent. All 12 lecturers successfully developed structured mentoring plans, and 24 student proposals reached the seminar-ready stage. Theoretically, these findings strengthen the relevance of the experiential learning approach in developing lecturers' academic competence. Practically, this program provides a replicable intervention model for private universities in standardizing the quality of thesis supervision at the master's level.